Prospects of Avocado Cultivation in Lebong Regency - Indrayanto Indrayanto (PT. Altaf Publishing Corp, 2024)
Avocados have significant potential to be developed as a leading commodity. A feasibility analysis is an important approach in evaluating the prospects of avocado farming. This study aims to analyze the prospects of avocado cultivation from a business feasibility perspective as well as from the aspect of nutritional content. The analytical methods used to evaluate the business prospects of avocado cultivation include cost analysis, revenue analysis, and the R/C ratio. The analysis of avocado prospects from a nutritional content aspect is conducted through a literature review. From a nutritional standpoint, avocados have excellent content, being rich in healthy fats, fiber, vitamins, and minerals; they also serve as antioxidants and sources of folic acid. Avocados are considered to have various advantages, including high market value, diverse varieties, availability of land and technological resources, and potential market absorption in both fresh and processed forms domestically and internationally.